A Changing of the Guard: Immune Checkpoint Inhibitors With and Without Chemotherapy as First Line Treatment for Metastatic Non-small Cell Lung Cancer - Pacheco, Jose M.; Camidge, D. Ross; Doebele, Robert C.; Schenk, Erin (Frontiers in Oncology, 2019)
Since approval of nivolumab as second line therapy for metastatic squamous non-small cell lung cancer (NSCLC) in 2015, first line treatment options for NSCLC have rapidly evolved to include checkpoint inhibitors [1]. Under normal conditions, the immune checkpoints programmed death protein 1 (PD-1), programmed cell death ligand 1 (PD-L1) and cytotoxic T lymphocyte antigen-4 (CTLA-4) are best understood as controls for activated T cells that limit their subsequent detection and responsiveness to antigen [2]. Checkpoint inhibitors that block PD-1 (nivolumab and pembrolizumab) or PD-L1 (atezolizumab, durvalumab and avelumab) prevent T cell downregulation initiated by PD-1 binding PD-L1 expressed on tumor cells and immune cells [3]. Ipilimumab and tremelimumab prevent the interaction of CTLA-4 on T cells with CD80 or CD86 on antigen presenting cells, allowing CD28, the co-receptor necessary for effective T cell stimulation, to bind [4]. Currently, a PD-1 axis inhibitor is recommended as first line therapy alone or in combination with chemotherapy for most patients with metastatic NSCLC, excluding those with a targetable oncogene such as ALK and EGFR [1]. Here we review the clinical data in support of the current approaches across histologies and biomarker subtypes, as well as highlight the future research directions revealed by the current data.